PENGARUH KOMITMEN TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL INTERVENING - Astuty, Isthofaina; Yuliana, Yuli (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2023)
This research has a purpose to analyze the effect of commitment on employee performance with motivation as an intervening variable. The subjects in this study were employees of the cleaning service unit, parking unit, and security unit at PT. Bummy Harapan Umat (BUHARUM) totaling 95 people. This research uses SPSS Statistics version 21 software and the analytical technique used is path analysis. Based on research that has been done at PT. Bummy Harapan Umat results obtained that commitment has a positive and significant effect on motivation, motivation has a positive and significant effect on employee performance, commitment has a positive and significant effect on employee performance, and motivation does not mediatecommitment to employee performance.